Antineutrophil antibody: a test for autoimmune primary sclerosing cholangitis in childhood? - Lo, S; Chapman, R; Cheeseman, P; Charlton, C; Walker-Smith, J; Mieli-Vergani, G; Fleming, K (1993)
The detection of an antineutrophil antibody which is highly sensitive and specific for adult primary sclerosing cholangitis using indirect immunoalkaline phosphatase has been previously described. In this study, the diagnostic potential of this method in childhood primary sclerosing cholangitis is described. A range of 72 blinded children's sera (36 boys), aged six months to 21 years (10 primary sclerosing cholangitis, eight autoimmune chronic active hepatitis, 10 alpha-1 antitrypsin deficiency, 12 extrahepatic bile duct atresia, 11 ulcerative colitis and 21 normal subjects) was assayed. Eight of the 10 primary sclerosing cholangitis patients were correctly identified. Three patients with chronic active hepatitis also showed the characteristic primary sclerosing cholangitis pattern of staining. No ulcerative colitis patients or any other patients showed this pattern of staining. All normal subjects were negative. As in adult primary sclerosing cholangitis, there is a specific antineutrophil antibody in childhood primary sclerosing cholangitis and this provides further evidence towards an autoimmune aetiology of this condition. The test may have diagnostic potential.